Scallops : biology, ecology, aquaculture and fisheries - Shumway, Sandra E.; Parsons, G. Jay (Amsterdam : Elsevier Science, 2015)
Scallops: Biology, Ecology, Aquaculture and Fisheries, Third Edition, continues its history as the definitive resource on scallops, covering all facets of scallop biology, including anatomy, taxonomy, physiology, ecology, larval biology, and neurobiology. More than thirty extensive chapters explore both fisheries and aquaculture for all species of scallops in all countries where they are fished or cultured. This treatise has been updated to include the most recent advances in research and the newest developments within the industry. As aquaculture remains one of the fastest-growing animal food-producing sectors, this reference becomes even more vital. It has all the available information on scallops needed to equip researchers to deal with the unique global issues in the field.
Previous edition: 2006.
Includes bibliographical references and index.
CHAPTER 1. Reconciling Morphological and Molecular Approaches in Developing a Phylogeny for the Pectinidae (Mollusca: Bivalvia)>CHAPTER 2. Biology and Ecology of Scallop Larvae>CHAPTER 3. Structure and Function in Scallops>CHAPTER 4. Scallop Adductor Muscles: Structure and Function>CHAPTER 5. Neurobiology and Behaviour of the Scallop>CHAPTER 6. Reproductive Physiology>CHAPTER 7. Physiology: Energy Acquisition and Utilisation>CHAPTER 8. Nutrition in Pectinids>CHAPTER 9. Scallop Genetics and Genomics>CHAPTER 10. Diseases and Parasites of Scallops>CHAPTER 11. Scallop Ecology: Distributions and Behaviour>CHAPTER 12. Swimming in Scallops>CHAPTER 13. Scallops and Marine Contaminants>CHAPTER 14. Dynamics, Assessment and Management of Exploited Natural Populations>CHAPTER 15. Scallops in Western North America>CHAPTER 16. Fisheries Sea Scallop, Placopecten magellanicus>CHAPTER 17. Scallops in Eastern North America>CHAPTER 18. Quantifying and Managing the Ecosystem Effects of Scallop Dredge Fisheries>CHAPTER 19. European Fisheries>CHAPTER 20. European Aquaculture>CHAPTER 21. Scallop Fisheries and Aquaculture in Japan>CHAPTER 22. Scallops and Scallop Aquaculture in China>CHAPTER 23. Scallops of Northwestern Pacific, Russian Federation>CHAPTER 24. Aquaculture of the Scallop Nodipecten nodosus in Brazil>CHAPTER 25. Scallops Biology, Fisheries and Management in Argentina>CHAPTER 26. Scallop Fishery and Aquaculture in Chile: A History of Developments and Declines>CHAPTER 27. Scallop Aquaculture and Fisheries in Venezuela>CHAPTER 28. Scallop Fishery and Culture in Peru>CHAPTER 29. Scallop Fisheries and Aquaculture in Mexico>CHAPTER 30. Scallop Fisheries, Mariculture, and Enhancement in Australasia.
CIP data; item not viewed.
Keywords: Scallop culture; Scallops -- Ecology; Scallop fisheries; Scallops; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Scallop culture; Scallop fisheries; Scallops; Scallops -- Ecology; Electronic books